KYRGYZSTAN AFTER THE REVOLUTION: POLITICAL DEVELOPMENT AND CHOICE OF FORM OF GOVERNMENT - KURMANOV, Zaynidin (CENTRAL ASIA AND THE CAUCASUS, 2006)
In the wake of the March 2005 events, a Constitutional Conference of the Kyrgyz Republic was convened on the initiative of Ch. Baekova, chairperson of the republic’s Constitutional Court, and a decision of Zhogorku Kenesh (the parliament). It met in Bishkek to discuss the political and constitutional reforms the country badly needed after the revolution. The one hundred and four-teen people who attended the conference represented the head of state, the cabinet, the deputies, and the civilian sector. Omurbek Tekebaev, speaker of the newly elected Zhogorku Kenesh, a very popular opposition member and leader of the Socialist Ata Meken Party, was elected the confer-ence chairman. At first, the political demands were moderate and boiled down to a political assessment of the events of 24 March and limiting some of the president’s powers. The next president should be de-prived of the right to organize referendums at will and to amend or change the Constitution. The pre-mier, on the other hand, should be given more power when it comes to appointing ministers. It was decided to restore the parliament’s former (105 against 75 deputies) numerical strength; and to elect two-thirds of its deputies on the basis of proportional representation as a step toward more developed party democracy. By 15 May, 2005, the amended Constitution was ready for publication. Supported by the civilian sector, it appeared in the local media. Kurmanbek Bakiev, the prime minister and acting president, surprised many by remaining ab-solutely indifferent to the prospect of constitutional reform. He was busy readying for the presidential election, scheduled under parliamentary pressure for 10 June, 2005. Part of the country’s political elite, however, insisted on immediate constitutional reform, after which the president (who would have different powers) could be elected. The hastily organized election was fraught with another political crisis caused by the bitter rivalry between the North and the South. This would have deprived the republic of its revolutionary dynamics and democratic conquests. The revolutionary leaders spared no effort to pacify the democratically minded public, while the two recognized leaders who formed a “political tandem”—Kurmanbek Bakiev, who represented the South, and Felix Kulov, who represented the North—entered an agreement and promised to carry out the constitutional reform. The tandem won the elections with about 90 percent of votes; Kurmanbek Bakiev became president, while Felix Kulov was presented to the parliament as a candidate for premier under the previous agreement between them. What happened next defied logic, but we should hardly have expected anything different from the new rulers. The new elite turned out to be an exact copy of the old one. The years of independence taught it what to do. The disillusioned revolutionaries, politicians, and ordinary people all say: “This is the old power with new names.”